Influence of Different Templates on Crystal Growth of Calcium Oxalate - YUE, WENJIN; DING, CHUNMEI; NIE, GUANGJUN; RONG, HUAICHAO (Asian Journal of Chemistry, 2010)
Crystal growth of calcium oxalate in bulk aqueous solution, human serum albumin template, uric acid template and mixed template containing human serum albumin and uric acid was studied in this paper. Calcium oxalate crystals were characterized by scanning electron microscopy, fourier transform infrared spectroscopy and x-ray diffraction spectrum. The results showed that different from manifold crystal morphologies of calcium oxalate formed in bulk aqueous solution, human serum albumin promotes the formation of calcium oxalate trihydrate, uric acid is propitious to the orientation growth paralleled with (020) plane for calcium oxalate monolydrate, but in the induction of mixed template, the orientation growth almost paralleled with ( 1 01) plane for calcium oxalate monolydrate. It suggested that different templates promote crystal growth of different calcium oxalate hydrate selectively. Furthermore, it could be concluded that human serum albumin template may be the depressor of kidney stone. But mixed template containing human serum albumin and uric acid may be the accelerant of kidney stone.